2006
DOI: 10.1152/ajpheart.01211.2004
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal but not circumferential deformation reflects global contractile function in the right ventricle with open pericardium

Abstract: The clinical evaluation of right ventricular (RV) contractility is problematic because instantaneous RV volumetry is difficult to achieve. Our aim was to test whether global RV contractility can be assessed by using regional indexes in the longitudinal and/or circumferential axis. Six anesthetized adult ewes were instrumented with a RV conductance catheter and four RV free wall sonomicrometry crystals (interrogating the longitudinal and circumferential axes). Global and regional preload recruitable stroke work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(33 citation statements)
references
References 33 publications
0
32
0
1
Order By: Relevance
“…[66][67][68][69][70] Assessment of longitudinal RV lateral wall performance can be performed through M-mode, 2-dimensional, tissue Doppler, and deformation imaging. Of these, tricuspid annular planar excursion (TAPSE) is most easily measured and accessible and has been evaluated in adult PAH.…”
Section: Longitudinal Global and Regional Functionmentioning
confidence: 99%
“…[66][67][68][69][70] Assessment of longitudinal RV lateral wall performance can be performed through M-mode, 2-dimensional, tissue Doppler, and deformation imaging. Of these, tricuspid annular planar excursion (TAPSE) is most easily measured and accessible and has been evaluated in adult PAH.…”
Section: Longitudinal Global and Regional Functionmentioning
confidence: 99%
“…Longitudinal systolic strain measurement is also especially well suited to assess RV function because RV contractility predominantly occurs in the longitudinal plane due to the principal orientation of myocardial fibers. 33 Previous studies have demonstrated feasibility for measuring RV strain using speckle-tracking echocardiography in PH 34,35 and other causes of RV dysfunction. [36][37][38][39] However, these studies included limited numbers of patients with PH.…”
Section: Discussionmentioning
confidence: 99%
“…The longitudinal contribution to total RV output has been shown to be approximately 80% owing to a predominantly longitudinal muscle fibre orientation. [7][8][9] For this reason, TAPSE, a measure of longitudinal displacement, has become popular in the rapid and simple assessment of RV function. [10][11][12] Tricuspid annular systolic plane excursion is independent of age, sex, and body size 11 ; however, it remains dependent on LV function.…”
Section: Discussionmentioning
confidence: 99%